Immunogenic variation among the so-called LC strains of Mycoplasma mycoides subspecies mycoides. - Smith, G. R. (Cambridge University Press, 1983)
Much evidence of immunogenic heterogeneity among the LC strains of Mycoplasma mycoides ssp. mycoides emerged from cross-immunization and -hyper-immunization experiments in mice in which three LC strains (Vom/Plum Island, 74/2488, and Mankefår 2833) were used for challenge purposes. All heterologous LC-strain vaccines cross-immunized against the three challenge strains, but protection was usually only 'partial', i.e. significantly less than that given by homologous vaccine. Cross-hyperimmunization with all heterologous LC but not SC strains produced protection against challenge with Vom/Plum Island that was virtually 'complete', i.e. similar to that produced by homologous vaccine. Challenge with 74/2488 gave generally similar results; but against Mankefår 2833 six heterologous LC vaccines gave complete protection and six did not. Vaccines prepared from the Smith (1423) strain of M. mycoides ssp. capri gave some protection against Vom/Plum Island but none against 74/2488 or Mankefår 2833. The cross-immunizing ability of three further M. mycoides ssp. capri strains appeared to resemble that of Smith (1423). In a cross-hyperimmunization experiment, vaccines prepared from SC strains of M. mycoides ssp. mycoides varied greatly in their ability to protect against challenge with strains 74/2488 and Mankefår 2833.